Developmental characteristics of firesetters: Are recidivist offenders distinctive?. (29th June 2018) - Bell, Ryan; Doley, Rebekah; Dawson, Deborah
Abstract : Introduction: This study examined the prevalence of developmental disadvantage and the extent that disadvantage could differentiate between recidivist and one‐time firesetters in an Australian sample of firesetting offenders. Methods: Variables pertaining to developmental experiences were collected from file data held by the Western Australian Department of Corrective Services pertaining to all offenders ( n = 354) convicted of a firesetting offence between 2005 and 2010. Analyses of variance were conducted between recidivistic and one‐time firesetters to investigate which developmental factors were related to risk of recidivism. Results: Based on previous research, it was hypothesized that firesetters would have poor developmental experiences characterized by high rates of abuse, parental absence, early substance use and poor educational achievement. This hypothesis was partly supported. Multiple firesetters were much more likely to be victims of childhood sexual and physical abuse and be diagnosed with a learning disability. Discussion: Current theories of firesetting maintain that an impoverished developmental experience catalyses the development of psychological risk factors that precipitate and maintain firesetting behaviour. The high prevalence of developmental risk factors among this population lends evidence to this relationship. Conclusions: These data suggest that physical and/or sexual abuse, the absence of a mother or father figure through childhood, problematic substance use, poor academic achievement and the presence of speech, learning and reading deficits are common among firesetters generally and the presence of childhood abuse and learning disability is a risk factor for repeat firesetting.